Hemorrhage of the second half of pregnancy in a national hospital of Lima - Acho Mego, Segundo (2015)
Objectives: To determine the frequency of hemorrhage in the second half of pregnancy. Design: Descriptive study. Setting: Department of Obstetrics and Gynecology, Hospital Nacional Cayetano Heredia, Lima, Peru. Participants: Pregnant women with second half hemorrhage. Methods: Review of 161 medical records from the Perinatal Information System of the Department of Gynecology and Obstetrics with diagnosis of hemorrhage of the second half of pregnancy in the period January 2008 through December 2009. Main outcome measures: Pregnant women characteristics and maternal and perinatal outcomes. Results: The 161 medical records analyzed represented 1.68% of obstetric care at the hospital. Age of women with hemorrhage of the second half of pregnancy was between 14 and 43 years with median 28 years; 62.7% (n = 101) had abruptio placentae, 34.8% (n = 56) placenta previa, and 2.5% (n = 4) uterine rupture (UR); 7,5% (n = 12) had adequate prenatal care, equal to or greater than 6 controls, and 92,6% (n = 149) less than 5 controls; 77,6% (n = 125) presented hemorrhage of the second half of pregnancy between 36 and 40 weeks of pregnancy, 13% (n = 21) between weeks 32 and 35. Hospitalization days were 3 to 20 days, with median 3 days. There were 16 stillbirths representing 9,9% of cases; lethality rate was 0,62%. Conclusions: Second half hemorrhage complicated 1,68% of the obstetric population during the study period and caused maternal and perinatal morbidity.